A new approach for smart electric meter based on Zigbee - Ahmed Shamil Mustafa; Mohamed Muthanna Al-Heeti; Mustafa Maad Hamdi (Institute of Advanced Engineering and Science, 2022)
A smart meter is an electronic device that accurately tracks your energy consumption and transmits that data to your energy provider so that you can be billed. The smart meters allow the central system and the meter to communicate in both directions. This two-way communication feature distinguishes the advanced metering infrastructure (AMI) in this case from automatic meter reading (AMR). This paper employs a hybrid system based on the Zigbee protocol, the Zigbee used to send messages between the smart meter and the utility company. To successfully complete tasks in this scenario, a cooperative communication system utilizing TDMA is used. The outcomes of Zigbee performance are measured using well-known metrics, also known as performance metrics. Many performance indicators have been chosen for performance evaluation: throughput, average end-to-end delivery ratio, and (PDR). The following conclusions were reached: End-to-end latency was 5.01 milliseconds, throughput was 42.63 kbps, and PDR was 97.19 percent. The network simulator successfully reads and wirelessly transmits voltage or power consumption using the Zigbee protocol and a cooperative communication system.